MENINGKATKAN PEMAHAMAN KONSEP SISWA DALAM TRANSFORMASI MELALUI PENERAPAN MODEL ECIPROCAL TEACHING - Yuni Susanto (Integral : Pendidikan Matematika, 2019)
ABSTRACT This research is a classroom action research with the objective to identify student development in concept comprehension of the subject of transformation as the application implications of reciprocal teaching model. Reciprocal teaching is a learning model that requires students to focus on four parts of activities in understanding the core material of the subject which are (1) question generating, (2) clarifying, (3) predicting, and (4) summarizing. These four activities of subject comprehension are conducted through LKS (Lembar Kerja Siswa). The subject of the research includes 32 students of XI Sciene 4 Class of SMA Negeri 2 Kota Cirebon year of 2019/2020. The implementation of this class action research is performed in three sequences of cycle with each sequence duration of 60 learning hours (6x45 minutes) of transformation subject. The instruments of this research is concept comprehension test (TPK). In the end of the cycle I, the average grade of TPK is 76,9 which is below the minimum criteria (KKM) of the third semester in SMAN 2 Kota Cirebon which is 78, and there are 15 students out of 32 students whose TPK grade is below the minimum criteria. In cycle II, action improvement is proceeded as an upgrade based on cycle I which is a change in the number of student in one group from 2 students to 4 students. This improvement results in an increase of average grade of TPK becoming 79,6, and a decrease of number of student with TPK grades under the minimum criteria becoming 12 students out of 32 students. Action improvement is also performed in cycle III as an upgrade based on cycle II by making more prediction phase on reciprocal LKS. This action improvement results in an increase of average grade of TPK becoming 83,3 and a decrease of number of student with TPK grades under the minimum criteria becoming 4 students out of 32 students. This result points out that the action proceeded in cycle III succeeds in minimizing the number of student with TPK grades under the minimum criteria into 12,5% which is under 15%; indicator of maximum number of student with TPK grade under the minimum criteria. This research concludes that the implementation of reciprocal teaching model has succeeded in improving student concept comprehension of the subject material of transformation. Keywords : comprehension, transformation, reciprocal teaching ABSTRAK Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk mengetahui peningkatan pemahaman konsep siswa dalam pokok bahasan transformasi sebagai akibat penerapan model reciprocal teaching. Reciprocal teaching adalah model pembelajaran yang menfokuskan siswa pada empat kegiatan memahami materi inti pokok bahasan. yaitu (1) question generating (membuat pertanyaan), (2) clarifying (menjelaskan), (3) predicting (memprediksi),dan (4) summarizing (merangkum). Empat kegiatan memahamai materi ini dipandu melalui lembar kerja siswa (LKS). Subjek penelitian ini adalah 32 orang siswa kelas XI IPA 4 SMA Negeri 2 tahun pelajaran 2019/2020. Penelitian tindakan kelas ini dilakukan sebanyak tiga siklus, yang masing-masing siklus dilakukan selama 6 jam pelajaran (6x45 menit), pada pokok bahasan transformasi. Instrumen peneliian ini adalah tes pemahamn konsep (TPK). Pada akhlir siklus I, rata-rata TPK adalah 76,9, masih berada di bawah nilai KKM SMA Negeri 2 Cirebon semester 3 yaitu 78, dan terdapat 15 siswa dari 32 siswa yang masih memiliki nilai TPK di bawah KKM. Pada siklus II dilakukan perbaikan tindakan sebagai hasil refleksi siklus I, berupa penguabahan jumlah siswa dalam satu kelompok dari 2 orang menjadi 4 orang. Hasilnya, pada TPK 2 terjadi peningkatan rata-rata menjadi 79,6, dan penurunan banyaknya siswa yang di bawah KKM menjadi 12 orang dari 32. Begitu pula pada siklsu III, dilakukan perbaikan tindakan sebagai hasil refeleksi siklus II, yaitu dengan cara menyempurnakan lembar kerja siswa reciprocal teaching pada fase perediksi di lipat gandakan menjadi dua kali dari jumlah prediksi pada LKS siklus I dan II, hasilnya adalah pada TPK 3 telah terjadi peningkatan rata-rata menjadi 83,3 dan telah terjadi penurunan banyaknya siswa yang memperoleh nilai di bawah KKM sebanyak 4 dari 32 orang. Berdasarkan hasil ini, maka tindakan pada siklus III telah berhasil menurunkan banyaknya siswa yang di bawah KKM adalah menjadi 12,5%, berada di bawah 15% yang menjadi indicator jumlah maksimal siswa yang memperoleh nilai di bawah KKM. Dengan demikian, penggunaan model reciprocal teaching telah berhasil meningkatkan pemahaman konsep siswa pada transformasi. Kata-kata kunci: pemahaman, transformasi, reciprocal teaching